Ziv-aflibercept in metastatic colorectal cancer - Patel A (Dove Medical Press, 2013)
Anuj Patel, Weijing Sun Division of Hematology-Oncology, University of Pittsburgh Cancer Institute, University of Pittsburgh School of Medicine, Pittsburgh, PA, USA Abstract: The combination of cytotoxic chemotherapy and antiangiogenic agents has become a conventional treatment option for patients with metastatic colorectal cancer. Ziv-aflibercept is a fusion protein which acts as a decoy receptor for vascular endothelial growth factor (VEGF)-A, VEGF-B, and placental growth factor (PlGF); it was approved in combination with 5-fluorouracil, leucovorin, and irinotecan (FOLFIRI) for the treatment of patients with metastatic colorectal cancer that is resistant to or has progressed after an oxaliplatin-containing fluoropyrimidine-based regimen. Herein we review the role of tumor angiogenesis as the rationale for antiangiogenic therapy, the clinical data associated with ziv-aflibercept, and its current role as a treatment option compared to other antiangiogenic agents, such as bevacizumab and regorafenib. Keywords: aflibercept, angiogenesis, colorectal cancer